Synchronizing Effects of Young Plantation of Dalbergia Sissoo Roxb. with Zea Mays in Agri-silvi Agroforestry System - Singh, R.B.; Singh, Charan; Ardey, Jayshree (Indian Forester, 2013)
One year old seedlings of Dalbergia sissoo planted at three different spacing of 4 x 4m, 5 x 5m and 6 x 6m along with control and hybrid maize crop (HQPM1) also grown at a spacing of 60 cm (as treatment-1) and 120 cm (as treatment-2) tree to crop line with three replications in Randomized Block Design. Average growth of height and collar diameter of Dalbergia sissoo was observed as 327.62 cm and 5.13 cm respectively when grown along with maize crop in all spacing. The maximum increase in height (189.78 cm) and collar diameter (4.77 cm) was observed in control with the tree spacing of 5m x 5m followed by initial height and collar diameter. The -1 -1 maize yield (with crop cover), of 38.21 qha-1 and stalk yield of 54.73-4 qha was found maximum in the tree spacing of 5m x 5m with 60cm tree to crop line spacing. The young plantation of D. sissoo at 5m x 5m distance with 60cm tree to crop line spacing of maize proved to be best combination giving maximum yield of maize crop in Agri-Silviculture agroforestry systems.